Management Of The Curriculum For Memorizing The Al-Qur'an - A Imaduddin Rizqunal Mahmudi; mundir mundir; Sofyan Tsauri (Institut Agama Islam An-Nawawi Purworejo, 2024)
The aim of this research is to analyze and describe the management of the curriculum for memorizing the al-Qur'an at Yasinat Islamic Boarding School Wuluhan Jember, its implementation and evaluation. The results of the research show that curriculum planning includes planning in the areas of (a) recruitment of prospective students who memorize the al-Qur'an, (b) the method of reading the al-Qur'an used, namely the Yanbu'a method, (c) independent memorization and muroja'ah collaborative, as well as (d) muhasabah, muqorrobah, and munajat. The implementation of the curriculum was organized by Kiai as a caregiver assisted by his sons as teacher of al-Qur'an memorization. Curriculum implementation is not only directed at successful habituation of memorization from the aspect of religiosity, but also success from the aspect of spirituality. This habituation is called the habituation and memorize religiosity and spirituality program. Curriculum evaluation is carried out in order to find existing strengths and weaknesses using the CIPP model (context, input, process and product).